The Human Rights Aspects Involved in the Implementation of Pregnancy Programs Through Non-Natural Methods - Salim, Stephanie; Noor, Tauchid; Adriano, Adriano (Jurnal Indonesia Sosial Sains, 2025)
This research aims to analyze the human rights aspects involved in the implementation of pregnancy programs beyond natural methods. The focus is on understanding the legal and ethical implications of assisted reproductive technologies (ART), such as in vitro fertilization (IVF), sperm and egg donation, and surrogacy. These technologies offer solutions for couples facing infertility but raise significant human rights and ethical issues, particularly regarding patient autonomy and the legal framework surrounding their use in Indonesia. The research methodology used in this thesis is normative juridical and the research approach utilizes a statutory, conceptual and comparative approach to examine national and international legal instruments, including the Indonesian Health Law and human rights conventions, to evaluate the extent to which they protect the rights of individuals undergoing ART procedures. The study found that while existing laws provide some level of protection, there are gaps and inconsistencies that may hinder the effective realization of reproductive rights. Recommendations include improving legal clarity and regulatory oversight, raising public awareness on reproductive rights, and ensuring that ART services are accessible and ethically implemented. By addressing these issues, this thesis aims to contribute to the development of a stronger legal framework that supports individual reproductive autonomy and upholds human rights in the context of assisted reproduction.